Understanding the Evolution of Cobalt‐Based Metal‐Organic Frameworks in Electrocatalysis for the Oxygen Evolution Reaction. Issue 15 (28th June 2021) - Cai, Xiaowei; Peng, Fei; Luo, Xingyu; Ye, Xuejie; Zhou, Junxi; Lang, Xiaoling; Shi, Meiqin
Abstract: Metal‐organic frameworks (MOFs) have attracted increasing attention as a promising electrode material for the oxygen evolution reaction (OER). Comprehending catalytic mechanisms in the OER process is of key relevance for the design of efficient catalysts. In this study, two types of Co based MOF with different organic ligands (ZIF‐67 and CoBDC; BDC=1, 4‐benzenedicarboxylate) are synthesized as OER electrocatalysts and their electrochemical behavior is studied in alkaline solution. Physical characterization indicates that ZIF‐67, with tetrahedral Co sites, transforms into α‐Co(OH)2 on electrochemical activation, which provides continuous active sites in the following oxidation, whereas CoBDC, with octahedral sites, evolves into β‐Co(OH)2 through hydrolysis, which is inert for the OER. Electrochemical characterization reveals that Co sites coordinated by nitrogen from imidazole ligands (Co−N coordination) are more inclined to electrochemical activation than Co−O sites. The successive exposure and accumulation of real active sites is responsible for the gradual increase in activity of ZIF‐67 in OER. This work not only indicates that CoMOFs are promising OER electrocatalysts but also provides a reference system to understand how metal coordination in MOFs affects the OER process. Abstract : Evolution 2 : Two types of Co based metal‐organic framework (MOF) are synthesized as electrocatalysts for the oxygen evolution reaction (OER) and their electrochemical behavior is studied in alkaline solution. The study indicates that Co‐based MOFs are promising OER electrocatalysts and provides a reference system to understand how metal coordination in MOFs affects the OER process.